2020
DOI: 10.1148/radiol.2019190878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contrast-enhanced US LI-RADS version 2017: Application on 2020 Liver Nodules in Patients with Hepatitis B Infection

Abstract: Background: Use of contrast material-enhanced (CE) US Liver Imaging Reporting and Data System (LI-RADS) version 2017 has not been validated in large populations where hepatitis B virus (HBV) is endemic. Purpose: To evaluate the diagnostic performance of CE US LI-RADS version 2017 in a population with a high prevalence of HBV infection. Materials and Methods: In this retrospective study, liver nodules in patients with HBV who were evaluated from January 2004 to December 2016 were categorized as CE US LR-1 to LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 32 publications
6
99
5
Order By: Relevance
“…The feature of washout within 60 s per LR-M criteria may be the primary reason why a substantial number of HCCs were classified as LR-M. In our study, 96.1% (124/129) of LR-M HCCs presented early washout, which is close to the results of 96% (214/224) in the study of Zheng et al[ 21 ]. Liu et al[ 13 ] found that the average washout time of ICCs was 27.5 s, compared with 70.1 s for HCCs ( P < 0.05).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The feature of washout within 60 s per LR-M criteria may be the primary reason why a substantial number of HCCs were classified as LR-M. In our study, 96.1% (124/129) of LR-M HCCs presented early washout, which is close to the results of 96% (214/224) in the study of Zheng et al[ 21 ]. Liu et al[ 13 ] found that the average washout time of ICCs was 27.5 s, compared with 70.1 s for HCCs ( P < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Some studies also demonstrated that the efficacy of marked washout in differentiating ICC from HCC can only be slightly improved even by postponing the onset time of marked washout to 3 min[ 15 , 18 ]. Zheng et al[ 21 ] found 142 out of 153 LR-M nodules showing early washout within 60 s and without punch-out before 5 min were HCCs. The authors re-categorized lesions showing the aforementioned washout patterns into LR-5, and the specificity and PPV of LR-M as a predictor of non-HCC malignancy were remarkably improved from 88% to 96% and 36% to 58%, respectively ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, only marked or early washout may not be the best criterion to rule out HCC as LR-M classification and further refinement of the LR-M category may be necessary. To improve the diagnostic performance of LR-M, Zheng et al [17] pointed out that if a nodule showing arterial phase hyperenhancement, early washout, and an ab-▶ sence of punched-out appearance within 5 minutes is reclassified as LR-5, then the LR-M specificity and PPV as a predictor of non-HCC malignancy would increase significantly. The clinical value of this new LR-M classification should be verified in a large multi-center prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the LR-M category (8% of lesions), 38% were ICC, 10% were mixed HCC-ICC, 48% were HCC, and 2% were metastases. A large study of 2020 patients with hepatitis B virus (HBV) infection from China validated CEUS LI-RADS® for patient populations in whom HBV is endemic -with LR-5 showing high specificity of 96% and positive predictive value of 98% for the diagnosis of HCC [44] . More recently, similar diagnostic accuracy was observed in another large retrospective study of patients from China who were predominantly (92%) HBV positivewith LR-5 showing a sensitivity and specificity of 73% and 97%, respectively for nodules 20 mm or less [45] .…”
Section: Discussionmentioning
confidence: 99%